El Gabinete de lectura del Ateneo Mexicano - López Zahar, Jocelyn Guadalupe (Pontificia Universidad Católica del Perú, 2021)
The Ateneo Mexicano, one of the first literary society in independent Mexico, was created to promote public education in that young country. The institution had its own Reading Cabinet. An inventory of books donated to the National Museum of Mexico shows that what kind of printed materials use to had the Ateneo’s library. That inventory was reconstructed and is presented in this article to reveal an important source of information, it shows the thematic variety of books, concerning with all topics of the classes given by Ateneo’s members.

El Ateneo Mexicano, una de las primeras asociaciones literarias del México independiente, fue creado para favorecer la instrucción pública del joven país. La institución tuvo su propio Gabinete de lectura. Un inventario de libros donados al Museo Nacional de México muestra qué impresos tenía la biblioteca del Ateneo, mismo que fue reconstruido y se presenta en este artículo para dar a conocer una valiosa fuente de información que denota la variedad temática de los libros, en relación con las materias de las cátedras impartidas por los ateneístas.
Ateneo Mexicano´s Reading Cabinet
Keywords: Ateneo Mexicano; literary society; Reading Cabinet; library; public instruction; Ateneo Mexicano; Asociación literaria; Gabinete de lectura; Biblioteca; Instrucción pública; https://purl.org/pe-repo/ocde/ford#6.01.01